A Morphological Study of Renal Arteries in Atherosclerosis – A Human Autopsy Study (Medical Forum Monthly, 2024)
Objective: To assess the different morphological changes in atherosclerotic lesions in renal arteries in relation to age and sexStudy design: Prospective descriptive observational studyPlace and Duration of Study: Mortuary of King Edward medical University and mayo hospital, Lahore, Pakistan. Duration of study was one and a half yearMaterials and Methods: A total of one hundred and thirty human autopsies were carried out during this study. Ninety were males and forty females. The age range was between 8 and 85 years. The autopsies were done left renal arteries were taken out artery for histological examination. Tissue processing was done. On the average 7-8 slides were prepared from each block by taking ribbons of tissues. The paraffin sections were stained using Haematoxylin and Eosin stain, Curtis’s picro-ponceau stain, verhoeff’s elastic tissue stain, von kossa’s staining technique, periodic acid Schiff (PAS) reaction, Toludine blue stain and peral’s Prussian blue stain.Results: The fibrolipid plaques were seen in 32 of the 39 cases seen on gross appearance in the right renal artery and 20 of the 24 cases seen on gross appearance in the renal artery. The complicated lesions were present in 15 cases in the right renal artery and 11 cases in the left renal artery. In the right 12 cases showed ulceration, 3 cases showed intimal vascularization and haemorrhage, whereas 2 of these cases also showed thrombus formation. In the left renal artery there were 8 cases showing ulceration, 3 cases showed intimal vascularization and haemorrhage and one of theses also showed thrombus formation. The calcified lesions were seen in 9 case in the right renal artery and 7 cases in the left artery. The morphological changes in the media and elastic were in 11 cases in right renal artery and 7 cases in left renal artery.Conclusion: Incidence of fibro-lipid plaques complicated and calcified lesion are quite high in both renal arteries. The relative high incidence of raised lesions in Right renal arteries may be due to more length, lower position and its position across the inferior vanacava.